Longitudinal associations between the disruption of incarceration and community re-entry on substance use risk escalation among Black men who have sex with men; A causal analysis. (1st August 2020) - Feelemyer, Jonathan; Dyer, Typhanye V; Turpin, Rodman E; Brewer, Russell A; Hucks-Oritz, Christopher; van Der Mei, Willem F; Cleland, Charles M; Mazumdar, Medha; Caniglia, Ellen C; Geller, Amanda; Scheidell, Joy D; Feldman, Justin M; et al.
Highlights: 1553 Black men who have sex with men were recruited from six cities in the US. Frequent drug use lowest for methamphetamine and highest for marijuana. Recent incarceration associated with binge drinking in adjusted analysis. Recent incarceration associated with crack use in adjusted weighted analysis. Need to consider alternatives to incarceration for substance using populations. Abstract: Background and Aims: While substance use can lead to incarceration, the disruptive effects of incarceration may lead to, or increase psychosocial vulnerability and substance use. Using causal inference methods, we measured longitudinal associations between incarceration and post-release substance use among Black men who have sex with men (BMSM), populations facing disproportionate risk of incarceration and substance use. Methods: Using data from the HIV Prevention Trials Network (HPTN 061) study (N = 1553) we estimated associations between past 6-month incarceration and binge drinking, marijuana use, and stimulant use post release (at 12-month follow-up visit). Adjusted models used inverse probability weighting (IPW) to control for baseline (pre-incarceration) substance use and additional risk factors. Results: There were 1133 participants present at the twelve-month follow-up visit. Participants were predominately non-Hispanic Blacks and unemployed. At baseline, 60.1 % reported a lifetime history of incarceration, 22.9 % were HIV positive and 13.7 % had a history of an STI infection. A total of 43 % reported a history of depression. In adjusted analyses with IPW, recent incarceration was associated with crack-cocaine (adjusted odds ratio (AOR): 1.53, 95 % confidence interval (CI): 1.03, 2.23) and methamphetamine use (AOR: 1.52, 95 % CI: 0.94–2.45). Controlling for pre-incarceration binge drinking, incarceration was associated with post-release binge drinking (AOR: 1.47, 95 % CI: 1.05, 2.04); in fully adjusted models the AOR was 1.14 (95 % CI: 0.81, 1.62). Incarceration was not associated with marijuana use. Conclusion: Findings underscore the need to provide substance use treatment in custody and post-release, and to consider alternatives to incarceration for substance using populations.